2013
DOI: 10.1177/0972150913501607
|View full text |Cite
|
Sign up to set email alerts
|

Financial System Development and Foreign Direct Investment: A Panel Data Study for BRIC Countries

Abstract: Developed financial system is one of the important determinants of Foreign Direct Investment (FDI). The article analyzes the impact of financial system development on FDI with respect to BRIC countries for the period 1991 to 2010. Using the panel data analyses, fixed and random effect, our results conclude that FDI inflows to BRIC countries are influenced by banking sector and stock market variables, used as a proxy for financial development. FDI is positively influenced by size of banking sector and stock mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 14 publications
4
59
0
1
Order By: Relevance
“…The function of financial institutions in host countries is essential because they provide the services to the foreign investors in terms of lower costs and quicker transactions, loans availability and better foreign exchange services. This result is similar to the findings of Hussain & Kimuli (2012) and Kaur, Yadava, and Gautam (2013).…”
Section: P-valuessupporting
confidence: 95%
“…The function of financial institutions in host countries is essential because they provide the services to the foreign investors in terms of lower costs and quicker transactions, loans availability and better foreign exchange services. This result is similar to the findings of Hussain & Kimuli (2012) and Kaur, Yadava, and Gautam (2013).…”
Section: P-valuessupporting
confidence: 95%
“…Consistent with Ezeoha and Cattaneo (2012), the impact of financial sector development on FDI is summarised into the allocative channel, economic efficiency and the liquidity easing theoretical rationales. Proponents of the allocative channel rationale including Kaur et al (2013), among others, argue that well developed financial markets are better able to increase foreign capital productivity through allocating financial resources to projects with a high rate of return. The economic efficiency rationale proposes that well developed financial markets have got the better capacity to ease information flow and reducing transaction costs thereby positively influencing FDI (Claessen and Laeven, 2003;Bartels et al, 2009;Ezeoha and Cattaneo, 2012).…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…Choong (2012:828) acknowledged that financial sector development must reach a certain minimum threshold point before FDI inflows positively and significantly influence economic growth in the host countries. In a panel study of BRICS (Brazil, Russia, India, China and South Africa) countries, Kaur et al (2013) reported that developed financial markets enable host countries to benefit from FDI through better provision of financial support in terms of quicker transactions, provision of loans, good foreign currency services and optimal allocation of capital to more deserving projects.…”
Section: Introductionmentioning
confidence: 99%
“…2015;Pan. 2003;Kaur et al, 2013) and section 4 of this paper and (2) data availability. Exports of goods and services (% of GDP), inflation, consumer prices (annual %), GDP per capita, domestic credit provided by the financial sector (% of GDP), total education expenditure by government (% of GDP), exchange rate (local currency/US$) respectively were used as measures for trade openness, inflation, economic growth, financial development, education and exchange rate, in line with majority of the prior studies on a similar subject matter.…”
Section: + Exchange Ratementioning
confidence: 99%